Quantitative easing in developed countries and middle income countries' financial markets - Ntuli, Thuthuka (My University, 2017)
This study examines Quantitative Easing policy programs of developed countries and their potential impact on Middle Income Countries through capital inflows. The study specifically focuses on the United States and European Union Quantitative Easing programs and investigates potential effects through the various transmission channels. An Autoregressive Multifactor MIDAS approach is used to carry out the empirical analysis and the study finds that lagged capital inflows are highly significant across the different models run and that there is evidence of transmission of quantitative easing to capital inflows to Middle Income Countries along the portfolio rebalancing and liquidity channels.
A research report submitted to the University of the Witwatersrand in partial fulfilment of the requirements for the degree of Master of Management in Finance and Investment.
Keywords: Capital movements; Quantitative easing (Monetary policy); Interest rates; Finance--Mathematical models